Sistem Keamanan E-Voting menggunakan Fungsi Hash dan Algoritma One Time Pad - Istiqamah, Nurul; Subiyanto, Subiyanto (Edu Komputika Journal, 2016)
The purpose of this paper is to develop an e-voting security system using a cryptographic hash function and the one-time pad algorithm. The security of e-voting system is applied through the fulfillment of the five aspects of information security that consist of confidentiality, authentication, data integrity, availability and non-repudiation. The implementation of e-voting security system is done by encryption the voting result. The encryption process is divided into two steps. First, by hashing the voting results using SHA-256 hash function then the hash value stored in the database. Second, by encryption the voting result using one time pad algorithm, this algorithm encryption process by performing XOR operation on plaintext and key that are generated using a random number generation approach. And then the description of the OTP algorithm is hashed using SHA-256 hash function. Both of hash value then compared, if it give a same value then the ballot is considered valid and safe from attacks during the transfer process to the server. This paper successfully meets five security aspects of e-voting system through the implementation of login system for confidentiality aspect, time validation and voters validation for authentication aspect, the encryption process during the elections for data integrity aspect, vote counting for availability aspect and time record for non-repudiation aspect.